Transcriptomic analysis reveals suppression of photosynthesis and chlorophyll synthesis following gibberellic acid treatment on oil palm (Elaies guineensis) - Chai, Sook Keat; Ooi, Siew Eng; Ho, Chai Ling; Ong Abdullah, Meilina (Springer, 2023)
Gibberellins (GA) and paclobutrazol (PBZ) are plant growth regulators. GA promotes plant growth and development while PBZ retards plant growth. Little is known about their effects on chlorophyll synthesis and photosynthesis in young oil palm plantlets. In this study, ten-month old young clonal palms were treated with 0.02 g/palm either gibberellic acid (GA3) or PBZ. The PBZ-treated palms were shorter with compact crown, shorter fronds and leaflets, more fronds and higher Soil Plant Analysis Development (SPAD) units, particularly at time point T1. Thus, PBZ suppressed elongation in leaflets, rachis and trunk but increased fronds production and leaf chlorophyll content. Contrastingly, GA3 promoted oil palm height with significant inter-leaflet elongation and lower frond production. Chlorophyll content was also adversely affected in GA3-treated palms at time point T1. Transcriptome sequencing revealed that differentially expressed genes (DEGs) were enriched for metabolic related activities. These genes were mostly downregulated by GA3 treatment. The GA3 treatment also reduced expression of chlorophyll synthesis genes, DEGs encoding components of the photosystems I (PSI) and II (PSII) supercomplexes, cytochrome b6f, Adenosine tri-phosphate (ATP) synthase and Rubisco as well as their assembly factors, translocons and photoreceptors. Meanwhile, PBZ treatment increased expression of geranylgeranyl diphosphate reductase that may inhibit GA biosynthesis but increase chlorophyll synthesis, which was likely correlated to increased chlorophyll content in the darker green leaves of PBZ-treated palms.